Analisis Penerapan Tax Planning PPh 21 Sebagai Upaya Efisiensi Pembayaran Pajak Perusahan PT XYZ - Aisyah Nabila Putri Mendropa; Syamsul Bahri Arifin; Iman I. K. Hasbulla (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to determine the application of the gross up method and the net method to calculate income tax article 21 on the amount of tax that must be paid by PT XYZ compared to the method currently used net method. This type of research is descriptive with a quantitative approach through observation and interviews. The results of this research by using the gross up method, PT XYZ can pay less corporate tax than using the net method to pay income tax article 21 which results in the company's net profit being greater.